Características epidemiológicas, clínicas y resultados del manejo quirúrgico del trauma abdominal cerrado en niños - Avalos Mendoza, Julio Miguel (2017)
AIM: To determine the epidemiological and clinical characteristics as well as the surgical management results of blunt abdominal trauma in children at Hospital Belén de Trujillo during 2006-2015. METHODOLOGY: An observational, descriptive, retrospective, case series study was performed in children with diagnosis of blunt abdominal trauma who were surgically operated. RESULTS: A total of 15 cases were studied, which 53.33% of them were men, the most frequent age group of 5 - 9 years (46.67%). Provinces of greater provenance: Trujillo (46.67%) and Otuzco (20%). The highest annual frequency recorded was 5 cases in 2008. Most frequent causal agents: traffic accidents (33.33%) and fall from different heights (26.67%). Most used image study: ultrasound (60 %). 60% were surgically operated lately. Most affected abdominal organ: small intestine (46.67 %). Most frequent extra abdominal injury: limbs (26.67%). Most common complication: nosocomial pneumonia (40 %). No deaths were reported. CONCLUSION: The main cause of blunt abdominal trauma was traffic accidents. The most commonly used imaging procedure was ultrasound. The most affected abdominal organ was the small intestine. The most frequent extra abdominal injury was in limbs. The most frequent complication was intrahospital pneumonia. The lethality rate was zero